2006
DOI: 10.1111/j.1365-3156.2006.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping malaria transmission in West and Central Africa

Abstract: SummaryWe have produced maps of Plasmodium falciparum malaria transmission in West and Central Africa using the Mapping Malaria Risk in Africa (MARA) database comprising all malaria prevalence surveys in these regions that could be geolocated. The 1846 malaria surveys analysed were carried out during different seasons, and were reported using different age groupings of the human population. To allow comparison between these, we used the Garki malaria transmission model to convert the malaria prevalence data at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 30 publications
8
96
2
2
Order By: Relevance
“…A significant proportion of countries in sub-Saharan Africa report human malaria prevalence in excess of 50% during 4-6·month transmission seasons (Omumbo et al, 2005;Gemperli et al, 2006). These observations would suggest that our experimental design of provision of effective concentrations of insulin at each bloodmeal for the duration of mosquito lifespan could faithfully represent feeding conditions in highly endemic areas, with the prediction that natural mortality patterns of feeding mosquitoes could be impacted.…”
Section: Discussionmentioning
confidence: 91%
“…A significant proportion of countries in sub-Saharan Africa report human malaria prevalence in excess of 50% during 4-6·month transmission seasons (Omumbo et al, 2005;Gemperli et al, 2006). These observations would suggest that our experimental design of provision of effective concentrations of insulin at each bloodmeal for the duration of mosquito lifespan could faithfully represent feeding conditions in highly endemic areas, with the prediction that natural mortality patterns of feeding mosquitoes could be impacted.…”
Section: Discussionmentioning
confidence: 91%
“…A key result of studies on human malaria is that temperature strongly influences malaria transmission [27,45]. For example, it has been shown to increase with a rise in the maximum monthly temperature [28]. Recent research has shown that the variation in diurnal temperatures is also a critical factor that affects the period of Plasmodium sporogony in mosquito hosts [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recent global maps created by the Malaria Atlas Project and Swiss Tropical Public Health Institute include uncertainty maps and use sophisticated statistical techniques to account for autocorrelation. 16,17 High-resolution maps may be useful for efficient and cost-effective targeting of interventions to the highest risk areas 8,12,[18][19][20][21][22] or in deciding to implement blanket coverage. The aims of this study were to generate and validate a high-resolution empirical risk map for household malaria risk in Nchelenge District, Luapula Province, Zambia.…”
Section: Introductionmentioning
confidence: 99%